Knallepulver, sockerbitar och mjältbrand - Jörgen Lundälv (Kulturella Perspektiv)
Concepts such as horror, threat and anxiety have become important in media history and in the risk society. This study deals with arsenic poisoning, anthrax attacks and trading with poison in the old and the modern society. Terrorism has developed in society and affects individuals' lives and welfare. Terrorism has also become a part of the media coverage and crisis journalism. The horror of poisoning is a part of history and will continue to be constructed as leading prime time news in the future.